Diversity and distribution of Lichens of Ambuluwawa Mountain - Silva, M.A.L.; Wijeratne, S.C. (My University, 2001)
Ambuluwawa Mountain in Gampola District reaches to a height of 1065 meters and vegetation is mostly disturbed. To study lichens three sites, each 100m, in area, at different elevations (high <990m), (mid 950- 870m) and (low 700- 650m) were selected. Three trees Alstonia macrophylla, Albizzia lebbek, Macaranga tomentosa were selected to study corticolous lichens. Alstonia macrophylla was present in all sites while Albizzia lebbek was present in sites one and three. Macaranga tomentosa was present in site two only. Rocks were used for sexicolous species. Total percentage lichen cover and the total number of different lichens were recorded by placing ...
Keywords: Diversity and distribution of Lichens of Ambuluwawa Mountain